Análise da administração de medicamentos por via intravenosa periférica e por hipodermóclise em idosos hospitalizados - Silva, Renata Martins da (2022)
Introduction: Patient Safety in drug therapy reiterates improvements in health care world wide, with comprehensive recommendations to improve the quality of care and administration of medicines, with the development of effective good practices in direct patient care. Infusional therapyis composed of peripheral intravenous therapy and subcutaneous therapy known as hypopoderliasis. Peripheral intravenous therapyis the most common invasive procedure among hospitalized patients, in the care of people who require intravenous drug therapy for the treatment of pathologies, whichenables the administration of solutions and/or medications, liquids, electrolytes and blood products in patients. Hypomorilysis is a therapy constituted in the modality of fluid administration for rapid correction of hydroelectrolytic imbalance that hás beengaining its space for use in patients under follow-up by the palliative care team, in the elderly and in debilitated patients. Objective: To analyze the use of hypopoderclise therapy compared to peripheral intravenous therapy in hospitalized elderly. Method: Cross-sectional observational study with quantitative approach, carried out in a large University Hospital, located in Porto Alegre/RS, Brazil. The sample consisted of 202 elderly patients, evaluated during hospitalization in relation to sociodemographic, clinical and related variables to peripheral intravenous therapyand/orhypopodercli is, contained in a data collection instrument. Data analysis was performed through descriptive and inferential statistics and all patients whoagreed to participate in the studys igned the Freeand Informed Consent Form. The research Project was approved by the Institution's Research Ethics Committee. Results: The evaluation of the 202 hospitalized elderly resulted in the predominance of the use of peripheral intravenous catheters in relation to the use of hypocardiac therapy, and it was evidenced that the complications resulting from the use of these drug administration routes were exclusive to intravenous therapy and focused on grade I and II phlebitis and grade I infiltration. Conclusions: This research allowed exploring the context of the use of IVT and HD in hospitalized elderly patients, verifying the imperative use of IVT when compared to hypopoderclilysis.